2012
DOI: 10.1111/j.1360-0443.2012.03845.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of behaviour change techniques to reduce excessive alcohol consumption

Abstract: It is possible to identify specific behaviour change techniques reliably in manuals and guidelines for interventions to reduce excessive alcohol consumption. In brief interventions, promoting self-monitoring is associated with improved outcomes. More research is needed to identify other behaviour change techniques or groupings of behaviour change techniques that can produce optimal results in brief interventions and to extend the method to more intensive interventions and treatment of alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
245
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 250 publications
(257 citation statements)
references
References 30 publications
7
245
0
5
Order By: Relevance
“…Hierarchical Cluster Analysis (HCA), the optimal number of groupings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were examined for suitability using measures of Internal Validity (Dunn's Index) and Stability (Figure of Merit, FOM) [34]. Bootstrap methods were used in conjunction with the HCA, whereby data were resampled 10,000 times, to identify which groupings were strongly supported by the data.…”
Section: : Investigating Hierarchical Structure Of the Bct Listmentioning
confidence: 99%
See 1 more Smart Citation
“…Hierarchical Cluster Analysis (HCA), the optimal number of groupings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were examined for suitability using measures of Internal Validity (Dunn's Index) and Stability (Figure of Merit, FOM) [34]. Bootstrap methods were used in conjunction with the HCA, whereby data were resampled 10,000 times, to identify which groupings were strongly supported by the data.…”
Section: : Investigating Hierarchical Structure Of the Bct Listmentioning
confidence: 99%
“…Identifying the presence of BCTs in intervention descriptions included in systematic reviews and national datasets of outcomes has allowed the identification of BCTs associated with effective interventions. Effective BCTs have been identified for interventions to increase physical activity and healthy eating [14] and to support smoking cessation [15,16], safe drinking [17], prevention of sexually transmitted infections [7,18] and changing professional behavior [19. Abraham and Michie [11] developed the first cross-behavior BCT taxonomy, building on previous intervention content analyses [7,8]. These authors demonstrated reliability in identifying 22 BCTs and 4 BCT packages across 221 intervention descriptions in papers and manuals.…”
Section: Introductionmentioning
confidence: 99%
“…Very often, this process continues until the treatment fails in contrast to another specific treatment [2] or, worse yet, in an effectiveness study where the method is pitted against usual care [3][4][5][6]. In meta-analyses that do not account for variation in control group magnitude, the end result is a small effect size [7]. The good news is that the field of addiction has a large array of evidence-based treatments for frontline practitioners to choose from.…”
Section: Branding Addiction Therapies and Reified Specific Factorsmentioning
confidence: 99%
“…The implication is that focusing upon and refining intervention techniques aimed at awareness and observation have the potential for boosting the effect sizes of smoking cessation intervention and, perhaps, addiction treatments overall. Indeed, there is a growing literature on the study of taxonomies of behavior change techniques which has recently shown specific techniques that predict reductions in alcohol consumption [7].…”
Section: Value Of Studying Treatment Techniquesmentioning
confidence: 99%
“…The central question here is whether specific therapy ingredients even exist and, if they do, are these ingredients strong enough to surpass the effects of a charismatic and passionate therapist, with high hopes for the client's potential and with strong skills in relating to others? There is also a set of core behavior change therapy techniques derived from a few established and longstanding treatment traditions [11]. With these conditions in mind, it seems inefficient to commit continued resources to the development of a truly novel (i.e.…”
Section: Branding Addiction Therapies and Reified Specific Factorsmentioning
confidence: 99%